Seeking the Sacred Online: Internet and the Individualization of Religious Life in Quebec - Meintel, Deirdre (Anthropologica, 2022)
Research I am conducting with colleagues on religion in Quebec today shows three main types of Internet use for re ligious purposes: (1) for building and maintaining contacts with other congregations and individuals within the same religious orientation on local and international levels; (2) for governance of religious groups at a distance; (3) accessing spiritual/reli gious resources (prayers, sermons, rituals). This technology can be used to reinforce transnational religious governance. At the same time, it contributes bo the individualization of re ligious life. I suggest that the findings of our team shed new light on religious individualization; that is, rather than implying superficial religiosity per se, individualization involves agency and self-responsibility for religious actors.